Determination of shaliness parameters of terrigenous rocks in cased boreholes and while drilling by radioactive logging combination - Bondarenko, Maksym; Kulyk, Volodymyr (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2024)
Introduction. Shaliness is an important lithological and petrophysical characteristic of reservoirs and seals in section of oil-and-gas boreholes as well as near-surface rocks (grounds) as the basis of buildings and engineering structures. Granulometric shaliness, determined by the presence of pelitic particles, and mineral shaliness, which characterizes the content of clay minerals, are distinguished in terrigenous rocks. In the sections of oil-and-gas fields, granulometric shaliness is one of the criteria for identifying reservoirs and affects their reservoir properties. The physical properties of reservoirs, which are studied by borehole logging, depend on the content and type of clay minerals. Information about clay minerals is taken into account when drilling and stimulation of hydrocarbon production. Shaly grounds apply to the group of cohesive ones, which in construction most often serve as the foundations of structures. At that these grounds are classified as difficult engineering-geological conditions for construction, since clay minerals specifically affect their strength, stability, etc. In oil-and-gas and engineering-geological boreholes the empirical equations relating gamma-ray logging readings and granulometric shaliness are most often used for quantitative estimation. Herewith, it is traditionally thought that the clay minerals make up the bulk of the pelitic particles. The paper is concerned with increasing the informativity of the borehole logging while investigating the shaliness of terrigenous oil-and-gas reservoirs and near-surface rocks based on a combination of gamma-ray logging, gamma-gamma density logging and neutron-neutron logging (GR+DL+NL). The investigation methodology included: borehole geophysical measurements by tools created at the Institute of Geophysics of the National Academy of Sciences of Ukraine independently and in collaboration with partner organizations; interpretation and analysis of logging data; justification and development of approaches to increase the informativity of the GR+DL+NL combination; estimation of the effectiveness of author’s developments using independent criterions. As a result of the investigation, on the basis of the abovementioned logging combination, the set of determined parameters is increased as compared with the traditional practice; number of new methods is developed for determining the parameters of shaliness, among them the content of clay minerals, their density and hydrogen index. The use of these parameters, in turn, improves the accuracy of porosity determination and other reservoir properties from logging data. Method for estimating the type of clay mineral according to the GR+DL+NL data is proposed. The method is an available alternative to geochemical core studies and to more expensive and difficult logging methods. The novelty of the developments is confirmed by patents, and their effectiveness is confirmed by the results of borehole tests and comparison with independent determinations of parameters (laboratory core examinations, control logging data). Practical significance. The proposed approaches are an important component of technologies for investigating oil-and-gas reservoirs and near-surface rocks, which are being developed at the Institute of Geophysics of the National Academy of Sciences of Ukraine.